Estudo da variação da porosidade ao longo do cordão em soldas subaquáticas molhadas - Ezequiel Caires Pereira Pessoa (2007)
There are many constructions projected and executed to satisfy the most diverse necessities of the human production around the world. A significant parcel of these structures is immersed in aquatic environments, mainly used for gas and oil industries. These structuresare projected to be resistant against innumerous types of damages. Thus, they should be safe to protect the operators and the environment for long time (25 100 years). Hence, it is of great importance that the maintenance and repair of such structures get towards with thestructural engineering requirements. Considering the environment in which they are, the repair and maintenance process becomes difficult, demanding special procedures that have been developed and applied for the petroliferous industry in the last years. Although with the reached evolution, the implemented repair techniques have not complied with the codes requirements. Underwater wet welding (UWW) with coated electrode is the preferred process because it offers advantages over the other available methods. Although underwater wet welding has been successfully applied in some situations, there are problems that have notbeen solved yet. Due to the water influence, this type of weld presents lower mechanical properties than dry welds. Porosity increases as water depth increases; it is difficult for the welder/diver to produce welds due to the conditions imposed from the environment. To minimize these problems, some processes have been tested as, chemical solutions, theapplication of special elements in the electrode covering, operational methods and use of special equipment. It is extremely important, for the evolution of the process, to reduce the porosity in this type of weld. Without porosity, underwater wet welds can be better classified and, therefore, applied in structural repairs and not only in emergencies or simply situations as are used actually. Previous study accomplished in surface conditions using stick electrodes shown that weld metal chemical composition changes along the weld bead. This variation was related to metal transfer mode alterations during welding. With the objective of detect changes in porosity along weld bead and makecorrelations with variations in metal transfer mode and weld metal chemical composition, it was tested different stick electrodes (commercial E6013 and E7018 and a experimental rutile tubular covered electrode), polarities and joints in simulated 50 and 100m water depths. The results shown that weld metal porosity is strongly dependant of electrode covering type, current polarity (for rutile electrodes type) and it reduces along weld bead. Weld metal chemical analysis and current and voltage signal investigation revealed that these porosity variations are strongly related with carbon oxidation (CO formation) and with short circuiting metal transfer mode occurrence. Also, it was observed that E6013 electrodes produce less porosity in UWW than E7018. This work also discusses, in an introductory way, the factors that can produces higher CO formation at the beginning of the weld bead and proposes amodel that makes correlations with this factors and porosity formation and variations in UWW.